DESIGUALDADES ECONÔMICAS INTERMUNICIPAIS, REGIONAIS E INTRAREGIONAIS NO ESTADO DO RIO DE JANEIRO: EVOLUÇÃO NO PERÍODO 1999-2008 - Andrade, Thompson Almeida (Geo UERJ, 2010)
doi: 10.12957/geouerj.2010.1485